Clinical Results Before and After Implementation of a Fast - Track Protocol For 507 Patients Who Underwent Total Knee Arthroplasty Surgery: A Retrospective, Observational Study (International Journal of Physiotherapy, 2022)
Background: Total knee arthroplasty (TKA) is a common surgical procedure for patients with advanced osteoarthritis. This study aimed to assess the effects of using versus not using a fast-track protocol, including a new mobilization device called Flexet.Methods: This is a retrospective comparative study. Two groups were formed with a total of 507 TKA patients. 283 were treated in 2010 with a standard program (S group) and 224 with a fast-track protocol (FT group) in 2016. The variables studied were active knee flexion and extension, length of stay, and time to autonomous gait.Results: Study groups were comparable. The mean time from surgery to autonomous gait was shorter for the FT group (4.43 hours, SD = 2.11) than for the S group (59.95 hours, SD = 16.59) (p < 0.001). Mean stay for the FT group was 2.36 nights (SD = 1.81) and 6.20 nights (SD = 1.52) for the S group (p < 0.001). Mean active flexion at hospital discharge was 89.33º (SD = 7.45) in the FT group versus 84.10º (SD = 9.01) in the S group. The mean active extension was: -5.37º (SD= 2.49) in the FT group versus -8.60º (SD = 3.98) in the S group, (p